STRATEGI DINAS LINGKUNGAN HIDUP DAN PERSAMPAHAN DALAM PENGELOLAAN SAMPAH PESISIR DI KOTA AMBON PROVINSI MALUKU - Regina Farfar (Institut Pemerintahan Dalam Negeri (IPDN), 2018)
Coastal waste management in Ambon City as a follow-up to Law Number 18 of 2008 and Ambon City Regional Regulation Number 11 of 2015 concerning Waste Management aims to make Ambon City as a waste-free city in 2025. Ambon City's environmental and solid waste department as the implementer of Ambon Government’s affairs in sanitation and environment sector is responsible for the realization of a good and comprehensive coastal waste management. But in the management implementation, the amount of coastal waste in Ambon still not showing any significant changes, so there’s still high possibility of obstacles in its implementation. This study aims to find out and analyze the implemented coastal waste management, to know and analyze the obstacles encountered in the implementation and to know and analyze the appropriate ideal strategies / concepts in coastal waste management. The theory used is the waste management theory proposed by Wilson, namely the aspects of regulation, institutions, funding, community participation and technology and strategy theory proposed by Wheelen and Hunger namely formulation, implementation and evaluation and supervision. This study used qualitative research methods. Data collection techniques used was interviews, observation, and documentation. The results showed that the environmental and solid waste department’s strategy in coastal waste management were not effective, this was evident from several aspects, namely the absence of regulating laws, institutional aspects that were not owned by the department, the aspect of technology which still conventional and the low rate of community participation. Therefore, in this study the authors convey several strategies or concepts in waste management, such as establishing strict laws and forming law enforcement officers, forming a special division to handle coastal waste, and increasing community participation through the establishment of yellow troops and the tourism ambassadors.